Mitigation of plate end debonding in CFRP strengthened wide-flange steel I-beams under monotonic and fatigue loading / Mohamed Kamruzzaman - Mohamed, Kamruzzaman (2017)
The use of the externally bonded reinforcement (EBR) technique with carbon fiber reinforced polymer (CFRP) is a recent and promising method for increasing the flexural capacity and fatigue life of steel structural elements. However, plate end-debonding is one of the main problems of CFRP strengthened steel beams. The CFRP end-debonding and end-delamination (EDL) causes premature failures for strengthened steel beams subjected to monotonic and cyclic loading, which is an essential issue that needs to be resolved. The aim of this study is to investigate the effectiveness of strengthening wide-flange steel I-beams using CFRP in order to increase the monotonic and fatigue flexural strength of the beams and improve against CFRP end debonding. This research highlights various approaches to improve the resistance against debonding by studying the CFRP in-plane end cutting shape, the combination of CFRP in-plane and tapering end shape, end anchorage, as well as the triangular spew fillet of adhesive at the tips of the CFRP plate. In addition, the effect of lateral bracing and stiffeners on the CFRP failure modes was also investigated. A total of twenty-five beams were fabricated and divided into two categories for the investigation, i.e. flexural monotonic and fatigue specimens. Furthermore, detailed finite element (FE) simulations have been conducted for the tested specimens. FE non-linear analyses has been carried out to simulate the flexural behavior of the beams under monotonic loading. The fatigue life was also predicted at constant load ranges for all tested steel beams using the FE simulations. The use of plate stiffeners and lateral bracing improve the overall performance of the strengthened beams. The application of the trapezoidal in-plane CFRP end cutting shape was found to be the best configuration for delaying the plate end debonding failure compared to the other end cutting shapes under both monotonic loadings and fatigue. Applying the combined trapezoidal in-plane and tapered CFRP end shape with triangular spew fillets of adhesive increased the load bearing capacity and delayed the plate debonding failure mode. Anchorage using CFRP fabrics at the end of CFRP plates mitigated the CFRP end problems, particularly end-debonding and EDL of strengthened beams. The FE simulation also showed that the trapezoidal is the best end cutting shape to delay plate debonding and the plate end anchorage using three layers with 220 x 175 mm CFRP fabrics is effective in mitigating end debonding initiation for monotonic and fatigue loading. The correlation between the results of the experiment and numerical modelling presented good agreements in this study.